Psychological support in events of mass destruction: challenges and lessons - Diaz, Joseph O Prewitt; Bordoloi, Sujata; Lakshminarayana, Rashmi (2004)
The 1990s saw the introduction and implementation of psychosocial support as an important component of disaster management programmes. This article presents a community-based psychosocial programme that seeks to address three challenges included assessment of the impact of a disaster on survivors, participatory planning to involve the community in support programmes and lastly the development and preparation of material to help the community help itself. -Reproduced.
Keywords: Disaster relief